A Dynamic Global Portfolio Immunization Strategy in the World of Multiple Interest Rate Changes: A Dynamic Immunization and Minimax Theorem - Khang, Chulsoon (Journal of Financial and Quantitative Analysis, 1983)
Chulsoon Khang, A Dynamic Global Portfolio Immunization Strategy in the World of Multiple Interest Rate Changes: A Dynamic Immunization and Minimax Theorem, The Journal of Financial and Quantitative Analysis, Vol. 18, No. 3 (Sep., 1983), pp. 355-363